Hubungan Usia Penyandang Diabetes Melitus Tipe 2 dan Disfungsi Ereksi - Panelewen, Rian; Rumbayan, Janette M.; Satiawati, Lusiana (e-Biomedik, 2017)
Abstract: Diabetes mellitus (DM) is a disease with high blood glucose level due to the inadequasy of insulin. Erectile dysfunction or inability to maintain an erection often occurs among males due to various factors. Males with DM have higher risk of erectile dysfunction compared to those without DM. This study was aimed to determine the relationship of the age of type 2 diabetes mellitus (T2DM) patient and erectile dysfunction. This was an analytical survey study with a cross sectional design. Respondents were all patients with T2DM at the Endocrine Polyclinic of Prof. Dr. R. D. Kandou Hospital Manado from October 2015 to January 2016. There were 38 respondents in this study; most had mild erectile dysfunction (36.8%). The Chi-square analysis showed a significant relationship (p<0.05) between the age of T2DM patients and erectile dysfunction. Conclusion: There was a significant relationship between the age of T2DM patients and erectile dysfunction. The older the patient, the more severe the erectile dysfunction.Keywords: diabetes mellitus, erectile dysfunctionÂ Abstrak: Diabetes melitus (DM) adalah penyakit dimana kadar glukosa dalam darah tinggi karena tubuh tidak dapat melepaskan atau menggunakan insulin secara adekuat. Disfungsi ereksi (DE) atau ketidakmampuan mempertahankan ereksi seringkali dialami oleh pria karena berbagai faktor. Laki-laki yang menyandang DM berisiko DE lebih tinggi dibandingkan dengan yang tidak menyandang DM. Penelitian ini bertujuan untuk mengetahui hubungan usia penyandang DMT2 dan tingkat DE. Jenis penelitian ialah survei analitik dengan desain potong lintang. Responden penelitian ialah semua pasien DMT2 di Poliklinik Endokrin periode Oktober 2015-Januari 2016. Hasil penelitian mendapatkan dari 38 responden, terbanyak yang mengalami DE ringan (36,8%). Berdasarkan analisis chi-square didapatkan hubungan bermakna (p <0,05) antara usia penyandang DMT2 dan DE. Simpulan: Terdapat hubungan bermakna antara usia penyandang DMT2 dan disfungsi ereksi. Semakin tinggi usia, semakin parah tingkat disfungsi ereksi yang terjadi.Kata kunci: diabetes mellitus, disfungsi ereksi